Pathophysiological mechanisms and therapeutic potentials of macrophages in non-alcoholic steatohepatitis. (3rd May 2016) - Wu, Ruonan; Nakatsu, Geicho; Zhang, Xiang; Yu, Jun
ABSTRACT: Introduction : Non-alcoholic steatohepatitis (NASH), a hepatic manifestation of metabolic syndrome, is a major cause of morbidity and healthcare burden worldwide. While the molecular pathogenesis of NASH remains unclear and therapeutic options are limited, inflammation is recognized as an essential factor for NASH development. Factors that link NASH to inflammation are macrophages and their secreted cytokines. Areas covered : This review summarizes the current knowledge of macrophage-mediated molecular pathways in NASH to shed insights on potential pharmacotherapeutic applications. Expert opinion : Macrophages are not only known for their role of phagocytosis in innate immunity, but also for both extrinsic and intrinsic regulation of inflammatory functions of many cytokines. Recent advances have revealed the effects of macrophage recruitment and polarization on the development of NASH. We and others have shown that the proliferation of hepatic macrophages and the subsequent production of pro-inflammatory cytokines initiates inflammatory cascades, orchestrates activities of transcription factors involved in lipid metabolism/translocation, and modulates programmed cell death. Together, these findings support the pathophysiological role of macrophages in the pathogenesis of NASH. Thus, evaluating potential therapeutic targets against the infiltration and/or polarization of specific macrophage subtypes is of clinical interest for alleviation of early-stage NASH, with the goal of halting disease progression.